2020
DOI: 10.1088/2515-7639/ab953c
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive relations for plasticity of amorphous carbon

Abstract: We deform representative volume elements of amorphous carbon obtained from melt-quenches in molecular dynamics calculations using bond-order and machine learning interatomic potentials. A Drucker-Prager law with a zero-pressure flow stress of 41.2 GPa and an internal friction coefficient of 0.39 describes the deviatoric stress during flow as a function of pressure. We identify the mean coordination number as the order parameter describing this flow surface. However, a description of the dynamical relaxation of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“… 268 Another study included the generation of many individual a-C model structures by GAP-driven quenching and a subsequent link to experimental properties. 269 A computational study of plasticity in large structural models of a-C, again using a combination of GAP and a faster empirical potential, was reported in ref ( 270 ).…”
Section: Applications (I): Force Fieldsmentioning
confidence: 99%
“… 268 Another study included the generation of many individual a-C model structures by GAP-driven quenching and a subsequent link to experimental properties. 269 A computational study of plasticity in large structural models of a-C, again using a combination of GAP and a faster empirical potential, was reported in ref ( 270 ).…”
Section: Applications (I): Force Fieldsmentioning
confidence: 99%
“…Mechanical properties of a-C have been reported in previous works 34,35 at room temperature. However, all of our fracture simulations are performed at zero temperature.…”
Section: B Calculation Of Mechanical Propertiesmentioning
confidence: 82%
“…Furthermore, it has been shown that the flow stress of a-C de-pends on the internal pressure of the cell which can be built up during quenching and mechanical loading. 35 Specifically Jana et al 35 observed a Drucker-Prager law with a zero-pressure shear flow stress of 41.2 GPa and an internal friction coefficient of 0.39. Thus the stress is a function of internal pressure and relaxing the internal pressure during the mechanical loading would decrease the measured stresses.…”
Section: B Calculation Of Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…An ML model constructed using the GAP methodology is obtained for amorphous carbon 88 . Deformation of the representative volume element of amorphous carbon is achieved by melt quenching using bond order and ML of the interaction potential between atoms 89 . The structure and elastic properties of low‐speed quenched amorphous carbon are investigated 90 …”
Section: Applicationsmentioning
confidence: 99%